Perbedaan Kejadian Astenopia Antara Pegawai Administrasi Dan Non Administrasi Fakultas Kedokteran Dan Kedokteran Hewan Universitas Nusa Cendana - Bryan Davidson Daruranto; Anita Lidesna Shinta Amat; Arley Telussa; Hyasinta Arlette Nikita (Universitas Nusa Cendana, 2025)
Administrative employees have a high risk of experiencing asthenopia due to long-term use of computers, but non-administrative employees with less duration of computer use can also experience asthenopia. incidence of asthenopia.Various symptoms of asthenopia were noted more frequently in workers using VDT (Visual Display Terminal) i.e. administrative employees than in workers who did little or no work using VDT, i.e. non-administrative employees. Knowing the difference in the incidence of asthenopia between administrative and non-administrative employees of the Faculty of Medicine and Veterinary Medicine, University of Nusa Cendana. This is a quantitative study with a case control design on employees of the University of Nusa Cendana. total sampling technique is used in this research. The sample was divided into administrative and non-administrative employees. Astenopia data were collected using a Computer Vision Syndrome questionnaire. Bivariate test using chi square showed a significant difference between administrative and non-administrative employees (p=0.000). Administrative employees have an average CVS score of 10.1 while non-administrative employees have 3.45. There is a significant difference in the incidence of asthenopia between administrative and non-administrative employees.